PENGARUH PEMBERIAN TEPUNG LARVA LALAT TENTARA HITAM (Hermetia illucens) TERHADAP KECEPATAN TUMBUH BURUNG PUYUH (Coturnix-coturnix japonica) - Ricky Selamet Rahayu; Ramadhani Eka Putra; Rika Alfianny (UIN Sunan Gunung Djati Bandung, 2021)
Quail (Coturnix-coturnix japonica) is a type of poultry that can be cultivated commercially because it has relatively fast growth and high productivity. Black Soldier Fly (BSF) is an insect that can be used as an alternative feed for quail in the form of flour because it contains high protein and fat which is friendly too for the environment. This study aims to determine the differences in the proximate content of each treatment; determine the difference in growth speed performance through the parameters of Initial Weight (IBW) and Final (FBW), Average Weight Gain (ABWG), and Body Length, determine differences in feed consumption parameters and feed conversion ratio (FCR) to weight gain; and determine which treatment yields the best performance for quail growth. This study used 80 quail with a feed composition of treatment A (100% commercial), B (25% BSF + 75% commercial), C (50% BSF + 50% commercial), D (75% BSF + 25% commercial), and E (100% BSF). The data were processed using IBM SPSS Statistics 25 software. The results showed that the highest proximate characteristics of water content, crude protein, crude fat, ash, fiber, calcium, and phosphorus were obtained in treatment E (100% BSF). The results of statistical analysis showed that there was a significant difference due to the provision of BSF flour to the growth speed parameters, that is the Final Body Weight (FBW) and the Feed Consumption parameter with the optimal treatment, that is treatment B (25% BSF + 75% commercial). The treatment that produced the best performance on quail growth speed was the provision of a feed mixture of 25% BSF flour and 75% commercial feed.